Phase formation and grain growth of BSCZT ceramics prepared by BST- BZT seed induced method - Jiraporn Dangsak (2018)
© 2018 Trans Tech Publications, Switzerland. In this work, lead-free Ba0.4Sr0.4Ca0.2Zr0.05Ti0.95O3(BSCZT) ceramics were prepared by the seed induced method using (0.5Ba0.6Sr0.4TiO3–0.5BaZr0.05Ti0.95O3) (BST-BZT) seed. Seed crystals with concentrations of 0, 2.5, 5, 7.5, 10 mol% were mixed with BSCZT powder for 24 h and sintered at 1400 °C for 4 h. The phase formation and microstructure of BSCZT ceramic were characterized by X-ray diffraction technique (XRD) and the scanning electron microscopy (SEM). All samples showed a single phase perovskite structure without impurities and exhibited the existence of the tetragonal phase. The density values of the ceramics decreased from 4.90 to 4.75 g/cm3with increasing seed crystal concentrations. The grain size of the sample without seed was 3.71 µm, whereas a grain size of 8.99 µm was observed for the sample with 10 mol% seed crystal. The dielectric constant at room temperature at 1 kHz was 1831 for the sample with 10 mol% seed crystal while the dielectric constant of the sample without seed was 1484. From the results in this work, BST-BZT seed can increase grain size and improve the dielectric constant at room temperature.